Advanced airway management in out-of-hospital cardiac arrest – to intubate or not to intubate: a narrative review of the existing literature - Saracoglu, Ayten; Saracoglu, Kemal (Anestezjologia Intensywna Terapia, 2020)
Restoring partial flow of oxygenated blood is a fundamental goal of cardiopulmonary resuscitation. The ideal devices used for this purpose should have features such as low incidence of complications, high survival rate, rapid control of the airway, and adequate ventilation. Besides limiting the frequency and duration of interruptions in chest compressions, they can improve the survival and clinical outcomes of return of spontaneous circulation during cardiopulmonary resuscitation. The overall rates of survival from out-of-hospital cardiac arrest have improved dramatically in recent years. However, optimal airway management during out-of-hospital cardiac arrest is a controversial issue. The proposed standard of care, i.e. endotracheal intubation, may have paradoxical adverse effects on intended outcomes by interrupting cardiopulmonary resuscitation and by reduction of coronary and cerebral perfusion pressure during resuscitation. The aim of this narrative review is to provide health care providers with an overview of relevant studies in the area, with a focus on alternative advanced airway techniques.